2013
DOI: 10.1186/2194-7511-1-11
|View full text |Cite
|
Sign up to set email alerts
|

Stability of lithium treatment in bipolar disorder - long-term follow-up of 346 patients

Abstract: BackgroundThe purpose of this study was to investigate the effectiveness and stability of long-term lithium treatment in a prospective, international, multicenter cohort of bipolar patients in a naturalistic setting.MethodsPatients were selected according to DSM IV criteria for bipolar disorder and required long-term treatment. They were prospectively followed and documented in five centers belonging to the International Group for the Study of Lithium-Treated Patients. This was a prospective cohort study witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 60 publications
0
20
0
2
Order By: Relevance
“…The number of manic episodes that a patient experiences has been associated with greater resistance to pharmacological treatment [8,9,22]. However, these findings were not replicated when the response to lithium was examined in a large 20-year follow-up study among adults with BD [23]. Concerning psychological interventions, cognitive behavioural therapy (CBT) and psychoeducational therapy have shown more effectiveness in the early stages of the disease compared with the later stages [24][25][26].…”
Section: The Life-time Course Of Bipolar Disordermentioning
confidence: 99%
“…The number of manic episodes that a patient experiences has been associated with greater resistance to pharmacological treatment [8,9,22]. However, these findings were not replicated when the response to lithium was examined in a large 20-year follow-up study among adults with BD [23]. Concerning psychological interventions, cognitive behavioural therapy (CBT) and psychoeducational therapy have shown more effectiveness in the early stages of the disease compared with the later stages [24][25][26].…”
Section: The Life-time Course Of Bipolar Disordermentioning
confidence: 99%
“…High variability is generally observed in patient response to treatment, which has led to several investigations of lithium’s mechanisms of action and the biological underpinnings of this response heterogeneity. Accordingly, the responsiveness to lithium has been particularly investigated in genomic studies and point to the existence of a distinct, more homogenous phenotype within BD patients (Alda et al, 2005; Grof et al, 2002; Scott et al, 2017) that appears to be stable across life (Berghofer et al, 2013). In addition, as seen in other diseases (Brunner-La Rocca et al, 2001; Potze et al, 2014), lithium might induce different effects in patients compared to controls, and understanding these diagnosis-specific effects might shed light into the genetic make-up of patients and its interaction with lithium.…”
Section: Introductionmentioning
confidence: 99%
“…This episodic recurrent form of BD is known to be associated with an increased rate of recurrent mood disorders, but not schizophrenia in relatives, and a high response rate to long-term lithium, estimated at 80%. 13,14 A recent large prospective study 15 of patients with classical BD reported that the morbidity index in lithium-treated patients remained stable for up to 20 years. Moreover, lithium response was found to cluster in affected members.…”
Section: Natural History and Heterogeneity Of Bipolar Disordermentioning
confidence: 99%